O papel do pediatra na investigação de doenças neuromusculares da infancia - Alexandra Prufer de Queiroz Campos Araújo; Clarisse Pereira Dias Drumond Fortes; Flavia Nardes; Eduardo Jorge; Salmo Raskin (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: Help the pediatrician in the suspicion of neuromuscular diseases when the child has complaints or altered findings in neuropsychomotor development, presenting one review on the topic. METHODOLOGY: Non-systematic literature review using articles published between 2015 and 2021 obtained with the terms "neuromuscular disorders" and "children"; "neuromuscular disorders" and "pediatric"; "milestones" and "delay"; "motor development" and "delay"; "development"and "neuromuscular disorders"; "neuromuscular disorder" and "evaluation"; "neuromuscular disorders" and "examination" in the Lilacs, Medline, Paho, Wholis and Scielo research bases. RESULTS: Data found in the review were compiled and divided into three topics: (1) Warning signs for neuromuscular diseases: how history and physical examination help define hypotonia and signs of muscle weakness; (2) Differential Etiological Diagnoses: most common clinical presentations and brief description of the main diseases with available therapies; and (3) Investigation of Neuromuscular Diseases: examples of situations divided between those with central or peripheral hypotonia, the use of creatine phosphokinase dosage in cases of muscle weakness and motor delay and examples of confirmatory tests of neuromuscular diseases with therapeutic possibilities. CONCLUSION: Although neuromuscular diseases are individually rare, they may have specific treatment that modifies their natural history, then the important differential diagnosis when there is a delay in neuropsychomotor development. It is imperative that the pediatrician, as a reference professional for families, have a high degree of suspicion and knowledge that allows initial assessment and referral to a specialized service.